2014
DOI: 10.1080/00405000.2014.927126
|View full text |Cite
|
Sign up to set email alerts
|

Quality and structural properties of gimp fancy yarns using the Design of Experiments

Abstract: The structure and quality characteristics of gimp fancy yarns were studied using an experimental design of seven factors with eight experimental runs. Non-gimp projections were considered to be structural defects; thus, they were counted and their numbers, average areas, and average circularity ratios were measured to account for those defects. Assigning the effects to factors and interactions was completed by taking into account gimp yarn structure and its manufacturing process. It was found that using two th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…Bending stiffness of input yarns was also thought to be important in defining the shape of the effect profiles of fancy yarns that have multiple-thread structure [8]. It was reported that a favourable fancy gimp yarn structure was achieved by choosing a material type for the effect thread that is sufficiently stiff.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bending stiffness of input yarns was also thought to be important in defining the shape of the effect profiles of fancy yarns that have multiple-thread structure [8]. It was reported that a favourable fancy gimp yarn structure was achieved by choosing a material type for the effect thread that is sufficiently stiff.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that a favourable fancy gimp yarn structure was achieved by choosing a material type for the effect thread that is sufficiently stiff. As it was found, using a relatively stiff bamboo ply yarn instead of a similar, but less stiff, cotton ply yarn created smaller non-gimp profiles, decreased their number and forced them to have a lower circularity ratio [8]. However, the authors did not use a method to measure the bending stiffness of the input yarns.…”
Section: Introductionmentioning
confidence: 99%
“…Researches relating to fancy yarns have mainly focused on three aspects: (1) the manufacturing techniques and properties of these yarns 1–3 and factors affecting their properties; 4,5 (2) the classification and application of fancy yarns; 6,7 (3) modeling studies based on yarn structures and properties. 8,9 Ring spinning techniques have attracted both researchers’ and manufacturers’ attention in developing various fancy yarn products from the relatively good yarn quality of the ring spinning process.…”
mentioning
confidence: 99%
“…Other important aspects of research into fancy yarn are their structure and geometry, and factors affecting their properties Fotheringham, 2014a, Alshukur andFotheringham, 2014b).…”
mentioning
confidence: 99%